Semipolar polycyclic aromatic compounds: Identification of 15 priority substances and the need for regulatory steps under REACH regulation. (20th March 2014) - Schwarz, Markus A; Behnke, Andreas; Brandt, Marc; Eisenträger, Adolf; Hassauer, Martin; Kalberlah, Fritz; Seidel, Albrecht
ABSTRACT Semipolar polycyclic aromatic compounds (sPACs) are frequently found in association with homocyclic polycyclic aromatic hydrocarbons (PAHs) in substances of unknown or variable composition, complex reaction products, or biological materials (UVCBs) from coal or crude oil and products derived thereof. However, major information deficiencies exist with regard to their prevalence and their toxicological and ecotoxicological potential, persistency, and bioaccumulation characteristics. Therefore, in this work, the environmental concern and relevance of sPACs was addressed in a general, stepwise approach. First, a large list of sPACs was collected and subsequently refined by assessing their persistence, bioaccumulation, and toxicity (PBT) properties by quantitative structure–activity relationship (QSAR) methods and their relevance by determining their respective frequency of occurrence. In this way, 15 priority sPACs were identified. These 15 priority sPACs were further characterized in detail with respect to their ecotoxicological properties, environmental behavior, carcinogenicity, and genotoxicity attributes. All of these 15 substances were quantified in distillate or product samples. In the next step, some principles for nomination of indicator substances, indicative for the overall content of sPACs, are derived. Data gaps on ecotoxicological endpoints preclude final conclusions, but the respective necessary supplemental tests were identified. Five of the 15 sPACs were tentatively characterized as potential substances of very high concern (SVHC) for the environment. The overall results of this study also clearly show that regulatory risk management of homocyclic PAHs within the European Regulation on Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) does not address the environmental concern created by sPACs within UVCBs from coal or crude oil. The study proves the need for additional regulatory steps under REACH and suggests indicator substances for their enforcement. Integr Environ Assess Manag 2014;10:415–428. © 2014 SETAC